Faktor-faktor yang mempengaruhi kepercayaan pengundi melayu terhadap Barisan Nasional di kawasan Utara - Abdul Salim, Tajudin (2018)
There are many issues arising out of the people's beliefs, especially the Malays against the Barisan Nasional leadership. Do the Malays still supporting the Barisan Nasional government or have turned to the opposition? The study aims to examine the factors that influence the Malay beliefs of the government based on five independent variables namely the performance of the leader, the performance of the government machinery, the national economy, the influence of mass media and the quality of life. The scope of study is limited to Malays living in Perlis, Kedah and Penang only. In this study, quantitative methods were used and the main data collection was carried out through questionnaire survey method. Questionnaire survey form is divided into eight sections. The strengths of the respondents were assessed using a Likert five-point scale. The study is based on three objectives and seven hypotheses. In this study, Malays of different ages, educational status, socio-economic status and different parliamentary constituencies were selected as the target population of the study. In this study, simple random sampling techniques were selected. A total of 1151 Malay voters comprising Kedah of 384 people, Penang 384 and Perlis 383 people were selected as sample surveys. Statistical techniques in the form of descriptive and inference have been used in this study include frequency analysis, Analysis of Variance (ANOVA) and Pearson correlation test. The findings show that people's trust towards the government is influenced by the performance factors of leaders, government machinery, national economy, mass media and quality of life. The most influential factor in Malay beliefs in the Barisan Nasional government was the mass media factor and followed by leadership performance factors. The mass media factor now known as social media and alternative media is the people's choice of information and is more popular and easily accessible anywhere without time and boundaries. Other factors are also a major cause in influencing people's beliefs.